Properties of Polymer Electrolyte Membranes Prepared by Blending Sulfonated Polystyrene with Lignosulfonate - Siang Tandi Gonggo; Cynthia L. Radiman; Bunbun Bundjali; I Made Arcana (Institute for Research and Community Services (LPPM) ITB, 2012)
A polymer electrolyte membrane widely used in PEMFCs and DMFCs is a perfluorosulfonated membrane (the Nafion membrane). This perfluorosulfonated membrane material exhibits good chemical stability and proton conductivity, but it is very expensive and difficult to recycle. There is a high methanol crossover in DMFCs that causes a decrease in efficiency and performance of the fuel cell, so that a polymer electrolyte membrane with a low methanol crossover is needed as a substitute for the Nafion membrane. One of the materials that can be used as a polymer electrolyte membrane is the polyblends from sulfonated polystyrene-lignosulfonate (SPS-LS). Such polyblends were prepared by casting a polymer solution and characterized as polyelectrolyte membrane for DMFCs. The SPS was prepared by sulfonation of polystyrene with acetyl sulfate as the sulfonating agent. The membranes of the SPS-LS were characterized by analysis of functional groups, mechanical properties and methanol permeability. The maximum mechanical properties of the SPS-LS membrane were observed at an LS ratio of 7.5%. However, the methanol permeability of the membrane increased with the increase of the LS ratio in the SPS-LS membranes. The properties of the membranes, especially their mechanical properties and methanol permeability, were close to that of Nafion® 117 membrane, so SPS-LS membranes have high potential for use as polymer electrolyte membrane for direct methanol fuel cells.